Analisis Kelayakan Isi Buku Teks Bahasa Indonesia Kelas X Terbitan Kemendikbudristek Edisi Revisi 2023 - Putri Dwi Archningtia; Ardhiana Syifa Miftahul Jannah; Siti Nadiyah Khasanah; Elen Inderasari (STIKes Ibnu Sina Ajibarang, 2026)
This research is motivated by the shortcomings in the Indonesian Language Textbook for Grade X Published by the Ministry of Education, Culture, Research, and Technology, Revised Edition 2023, in the form of inconsistent material presentation patterns, imbalance in linguistic and literary aspects, and unequal distribution of materials. This research study aims to assess the content suitability of the Indonesian Language Textbook for Grade X Published by the Ministry of Education, Culture, Research, and Technology, Revised Edition 2023. The method applied in this research is content analysis. The findings of this study indicate that chapters I to VI in the book have met or fulfilled the five indicators of content suitability according to Hartono (2016), although chapter IV is less suitable for the depth and breadth of material indicators because it does not include material on the structure of poetry. However, overall, this textbook is very suitable for use as a primary reference book in learning Indonesian. Thus, this study can be an evaluation material for textbook writers to complement the shortcomings in the next edition of new Indonesian language books.